PENGARUH CURRENT RATIO, RETURN ON ASSET DAN EQUITY PADA MODAL KERJA - Sudarti Sudarti; Herman Sjahruddin; Orfyanni S Themba; Ardiansyah Halim (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
This study aims to determine the effect of Current Ratio, Roa, and Roe on Working capital at PT. Unilever Indonesia, Tbk. The study population was the quarterly financial reports, 2008-2018 using by totalling sampling in sampling so that 4x11=44 data units were obtained as the sample. Data analysis used multiple linear regression through the use of SPSS Ver.25. The analysis shows that the current ratio and return on assets have a significant positive effect and the other causality showing return on equity has a significant negative effect on working capital.